Multiyear greenhouse gas flux measurements on a temperate fen soil used for cropland or grassland. Issue 1 (2nd January 2015) - Beyer, Colja; Liebersbach, Horst; Höper, Heinrich
Abstract: To date there is still a lack of reliable data on greenhouse gas emissions from drained fens needed to determine the climatic relevance of land use and land use change on peatlands and to supply the National Inventory Report for the German Greenhouse Gas Inventory. In this study we present the results of monthly‐based multiyear measurements of CO2, N2 O and CH4 flux rates in two drained agriculturally used fen ecosystems in NW Germany (cropland and grassland) over a period of 4.5 y using transparent and opaque closed chambers. CO2 exchange was modelled at high resolution with temperature and photosynthetic active radiation. The measured and modelled values fit very well ( R 2 ≥ 0.93). Annual GHG and Global Warming Potential (GWP) balances were determined. Net CO2 emissions at the cropland and grassland sites were similarly high, taking into account changes in management; net ecosystem C balance amounted to about 4.0 to 5.0 Mg C ha −1 y −1 . Emissions of N2 O and CH4 were low at both sites. The mean GWP balance for a time frame of 100 y (GWP100) amounted to about 17.0 to 19.0 Mg CO2 ‐eq. ha −1 y −1 . The unexpectedly low greenhouse gas emissions from the cropland site are attributed to the high water table and a change in crop management. The change from corn for silage to corn‐cob mix lead transiently to rather small greenhouse gas emissions. The study confirms the need for multiyear measurements taking climatic and management variation into account.